GEMF 52 (PGM XXIVa) A Hybrid Case of Greco-Egyptian Cleromancy? - Faraone, Christopher A. 1955-; Torallas Tovar, Sofía (2025)
This contribution analyzes the nature of GEMF 52/PGM XXIVa, a third century papyrus fragment with incomplete instructions for some kind of oracular consultation. We provide context to this papyrus through comparison with other Greek and Egyptian divinatory texts and artifacts, to understand the process of consultation and its methods.
Keywords: Greco-Egyptian mantic practices; cleromancy; magical formularies